Fighting child sexual abuse: perspectives of pupils from a developing country - Gwirayi, Pesanayi (SAGE Publications, 2021)
This study investigated secondary school pupils’ views on strategies that can be used to prevent child sexual abuse (CSA). A survey design was adopted as the operational framework for data gathering. Data were collected from three secondary schools, all in the Gweru district of Zimbabwe. The sample comprised 268 secondary pupils (50% female; M age = 15.42, SD = 1.376). Each participant was asked to write down three main strategies that can be used to fight CSA on a given questionnaire. The responses were then analyzed using the thematic content analysis technique. The study revealed that most pupils believed that CSA can be prevented through teaching them about it and also reporting to the police. Another significant finding was that pupils’ responses tended to vary with gender and level of education. Whereas female respondents suggested that CSA can be fought by avoiding strangers, saying no to sexual advances, and having reliable friends, their male counterparts suggested teaching the community about CSA, forming new clubs, and enacting life imprisonment for perpetrators, among other suggestions. In terms of level of education, Form 2 participants suggested avoiding strangers, staying home at night, whereas their Form 4 counterparts suggested lessons for Guidance and Counseling, saying no to sexual advances, and having reliable friends. These findings unequivocally demonstrate the need to vigorously engage secondary school pupils in activities aimed at fighting CSA to safeguard their inalienable human rights.